Effect of Profit Volatility, Dividend Policy, And Company Size on Stock Price Volatility in Banking Companies Listed On IDX in 2018-2022 Period - Harnanti, Nunti; Nurdiana, Diah (International Journal of Multidisciplinary Approach Research and Science, 2025)
This research set out to ascertain the impact of firm size, dividend policy, and earnings volatility on stock price volatility in banking companies listed on the Indonesian Stock Exchange (IDX). All banking businesses listed between 2018 and 2022 on the IDX are included in the research population. Using the purposive selection approach, the sample was selected based on the requirement that the corporation paid cash dividends and released financial reports during the study period. Nine firms were selected as a sample using the predetermined criteria. Secondary data is utilized. Multiple linear regression is the data analysis technique with a significance level of 0.05. The study's findings show that (1) earnings volatility does not influence stock price volatility. Dividend policy influences the volatility of stock prices. (3) Stock price volatility is unaffected by the company's size. (4) The simultaneous influence of Earnings Volatility, Dividend Policy, and Company Size on Stock Price Volatility is null. (5) The R-squared adjustment is 0.34. This indicates that 34% of the dependent variable's explanation may be attributed to independent factors, with the other 66% coming from variables not included in this research.